Rituximab Experience in Patients With Long-standing Systemic Sclerosis–Associated Interstitial Lung Disease: A Series of 14 Patients. Issue 8 (December 2017) - Sari, Alper; Guven, Denizcan; Armagan, Berkan; Erden, Abdulsamet; Kalyoncu, Umut; Karadag, Omer; Apras Bilgen, Sule; Ertenli, Ihsan; Kiraz, Sedat; Akdogan, Ali
Abstract : Objectives: The objective of this study was to report the experience with rituximab treatment in a case series of patients with long-standing systemic sclerosis–associated interstitial lung disease (SSc-ILD). Methods: We reviewed the charts of 197 SSc patients. Fourteen patients who received rituximab for SSc-ILD participated in this analysis. Pulmonary function tests, high-resolution thorax computed tomography and modified Rodnan skin scores were evaluated at baseline and end of the follow-up. Results: Median age was 53.2 years (interquartile range, 46.8–55.5 years), and median disease duration was 9.1 years (interquartile range, 5.1–13.6 years). At the end of median follow-up (15 months), although the median forced vital capacity value increased compared with baseline, the change was not statistically significant (52.5 vs. 58.0, P = 0.065). Forced vital capacity was improved in 4 patients and stabilized in 10 patients. High-resolution computed tomography was stable in 7 patients and worsened in 3 patients. Modified Rodnan skin scores remained stable at the end of follow-up (8.0 vs. 6.0, P = 0.6). Conclusions: The improvement or stabilization of pulmonary disease was observed in most SSc patients with longer disease duration and worse pulmonary function. Rituximab might be useful in this patient group who is resistant to conventional immunosuppressive treatments.